How Does Pikeperch Sander lucioperca Respond to Dietary Insect Meal Hermetia illucens? Investigation on Gut Microbiota, Histomorphology, and Antioxidant Biomarkers - Tran, Hung Quang; Prokešová, Markéta; Zare, Mahyar; Gebauer, Tatyana; Elia, Antonia Concetta; Colombino, Elena; Ferrocino, Ilario; Caimi, Christian; Gai, Francesco; Gasco, Laura; Stejskal, Vlastimil (Frontiers in Marine Science, 2021)
Effects of feeding dietary defatted black soldier fly (Hermetia illucens) larvae meal (HI) on intestine microbiota, and on histomorphology, oxidative enzyme activities in liver and intestine of pikeperch (Sander lucioperca) were investigated. Four isoproteic (45% crude protein) and isolipidic (18% ether extract) diets were formulated to include 0% (CO), 9% (HI9), 18% (HI18) and 36% (HI36) of HI as replacement for fishmeal at 0, 25, 50, and 100%, respectively, and were fed to triplicate groups of juvenile pikeperch (initial body weight, 68.7 ± 7.1 g) for 84 days. No adverse effects were detected on the intestine of pikeperch fed diet groups, in terms of histomorphology (P > 0.05), while fish fed free or low levels of HI (≤ 9% in diet) showed significant liver degeneration (P < 0.05). Dietary HI significantly affected the oxidative enzyme activities of catalase and glutathione peroxidase in the liver, and glutathione S-transferase in the intestine (P < 0.05), while activity of superoxide dismutase in both liver and intestine was HI-dose independent (P > 0.05). Feeding HI-containing diets positively modulated the richness and diversity of intestinal microbiota, especially for HI18 group (P < 0.05). Inclusion HI up to 18% (50% fishmeal replacement) in pikeperch diets increased abundance of Clostridium, Oceanobacillus, Bacteroides, and Faecalibacterium genera, whereas the predominant bacterium, Cetobacterium was found in control and HI36 groups. This study reveals the potential of HI as an immune and health booster for juvenile pikeperch.